The Cost-Effectiveness Analysis of Self-Efficacy-Focused Structured Education Program for Patients With Type 2 Diabetes Mellitus in Mainland China Setting - Jiang, Xinjun; Jiang, Hua; Tao, Libo; Li, Mingzi (Frontiers in Public Health, 2021)
Objectives: To assess the long-term (50 years) cost-effectiveness of the self-efficacy-focused structured education program as opposed to routine education among patients with type 2 diabetes mellitus (T2DM) in mainland China from a healthcare service perspective. Methods: A cost-effectiveness analysis method was used. The IQVIA CORE Diabetes Model (version 9.0) was adopted to estimate the outcomes. The baseline cohort characteristics, variations of physiological parameters, costs of intervention and other treatments, as well as management-related diabetes were derived from a randomized controlled trial. Moreover, the complications costs and utilities were extracted from published sources. Furthermore, univariate sensitivity analysis and probabilistic sensitivity analysis were conducted. Results: As compared with the control group, the life expectancy and quality-adjusted life-year in the intervention group were increased. Besides, the intervention group achieved lower cumulative incidences of complications, and saved more direct medical costs compared with the control group. The sensitivity analysis revealed that the SSEP had 100% probability to be cost-effective. Conclusions: The self-efficacy-focused structured education program is recognized as a highly cost-effective option for managing T2DM patients which are projected to both improve clinical outcomes and reduce costs.